(untitled) (Itinera, 2023)
Wunderkammern represent a truly interesting phenomenon not only because of their peculiar feature of collecting amazing, even monstrous, items from all over the planet, but especially for the importance given to feelings such as curiosity, wonder and astonishment in the process of discovering the world, as a medium to get to knowledge.Wunderkammern, also known as Cabinets of Curiosities, keep being represented in art and entertainment, with particular relevance to their most grotesque aspects; here, the focus is on two depictions coming from non-fiction children’s literature, which has gone through a recent wave of innovation regarding specifically the picturebooks form. The non-fiction picturebooks edited in the last decade appear to have in common a significant illustration and design apparatus, resulting in a strongly creative and aesthetic approach to knowledge: engaging the senses – and therefore inspiring awe and wonder – together with data and information, these non-fiction picturebooks contribute to restore value to art and beauty in the learning process, revealing a sort of relationship with the Wunderkammer paradigm.